UPAYA MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR ADMINISTRASI KEUANGAN MELALUI COOPERATIVE JIGSAW DI KELAS XI AP 5 SMK NEGERI 1 SOLOK - Desy Asmara (PAKAR Pendidikan, 2018)
The aim of the class room research was to find out activity and learning achievement can inrease to use Cooperative Jigsaw method in class XI AP-5 Senior High School 1 Solok City. The population of this research was all of 33 student in class XI AP-5 Senior High School 1 Solok City. All student is population of this reseach by using total sampling technique. The data were analyzed through percentase. Based on the analysis of data research, researchers managed to achieve success indicator studies in the second cycle, namely: (i) mastery learning achievement reached 92.00%, above the indicator that is 77%, (ii) Learning Activities 63.56% above the indicators set 50%. The conclusion of this study is the implementation of a Cooperative Jigsaw method can increase the activity of learning and learning achievement in class XI AP-5 High School 1 Solok City.